DŮM NA HRANĚ - Valašské Meziříčí, ulice Sokolská - Serenčko, Igor (Vysoké učení technické v Brně. Fakulta architektury)
Cílem Bakalářského projektu bylo navrhnout zástavbu do proluky ve Valašském Meziříčí, nacházející se v blízkosti historického centra města. Konceptem je kompaktní bytová zástavba s bydlením v 2-4.np, 1.np zahrnuje parkování a komerční parter. Cílem bylo navrátit parcele její původní funkci s maximálním využitím plochy parcely.

The aim of the project was to design a Bachelor installation in the vacant lot in Valasske Mezirici, located near the historical city center. The concept is a compact residential development with housing in a 2-4.np, 1.np includes parking and commercial partners. The aim was to return the plot to its original position with maximum use of surface plots.
HOUSE ON THE EDGE – Valašské Meziříčí, Sokolská Street
Keywords: dům na hraně; valašské meziříčí; polyfunkční dům; bakalářský projekt; house on the edge; Meziříčí; multi-functional building; Bachelor project